Effects of Timber Harvesting and Related Management Practices on Water Quality in Forested Watersheds - Sopper, William E. (Journal of Environmental Quality, 1975)
Abstract Undisturbed forested watersheds are generally recognized as a primary source of high‐quality water. The physical and chemical nature of these waters fluctuate constantly in response to natural stresses but are most influenced by man's activities. Three major forest land management activities—timber harvesting, fertilization, and herbiciding—which may have an adverse affect on water quality are reviewed. In general, research results indicate that nutrient losses, particularly nitrogen, following forest clearcutting are small to negligible. Similarly, forest fertilization studies indicate that nitrogen concentrations in streams are not drastically increased. Large areal applications of selected herbicides in the West have demonstrated that, if carefully applied, they can be used without impairment of water quality.
Keywords: Ouvrage_Collectif_Numéro1

Evaluating Alternative Techniques Floodplain Mapping - Wolman, M. Gordon (Water Resources Research, 1971)
A variety of techniques is available for providing information on the frequency and extent of flooding in river valleys. These techniques include the use of physiography, pedology, vegetation, occasional floods, regional floods of selected frequency, and flood profiles and backwater curves. Preliminary estimates of costs suggest that these range from a low of $1–4/mile of channel to a high of $400–1000/mile of channel. All estimates of flood hazards and damages contain significant uncertainties deriving from the variability and uncertainty of the estimates of hydrologic, hydraulic, and social phenomena. An accelerating demand for information coupled with recognition of the inherent element of judgment in any determination of flood or damage zones suggests additional emphasis on the adoption of different mapping techniques appropriate to the needs of different locations.
Keywords: Ouvrage_Collectif_Numéro1